Detection and assessment of victims of illtreatment and torture in Primary Health Care. : Quick guide including developments in the 2022 updated version of the Istanbul Protocol. - Pérez-Sales, Pau; de la Fuente, Paula (Torture Journal, 2023)
Editorial